2012
DOI: 10.1590/s1983-14472012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes vivendo com HIV/AIDS e coinfecção tuberculose: dificuldades associadas à adesão ou ao abandono do tratamento

Abstract: Pesquisa realizada em Fortaleza-CE, entre março e abril de 2011, com o objetivo de identificar as dificuldades que influenciam a adesão ou o abandono do tratamento de tuberculose em pacientes com Síndrome da Imunodeficiência Adquirida. Estudo qualitativo, com informações coletadas por meio de entrevista semiestruturada aplicada a pacientes com Síndrome da Imunodeficiência Adquirida e coinfecção tuberculose. Utilizamos o discurso do sujeito coletivo para a análise dos resultados. Os pacientes relataram dificuld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
2
15
0
4
Order By: Relevance
“…20 This study showed that most of the patients interviewed did not use tobacco and alcohol, which is an important factor to adherence to treatment, as also found in a study carried out in Fortaleza, in the state of Ceará. 21 The health centers in the municipality of Campinas have groups to assist different types of conditions, but there is no group for TB patients although they and the professionals have reported offering/receiving this action, respectively.…”
supporting
confidence: 75%
“…20 This study showed that most of the patients interviewed did not use tobacco and alcohol, which is an important factor to adherence to treatment, as also found in a study carried out in Fortaleza, in the state of Ceará. 21 The health centers in the municipality of Campinas have groups to assist different types of conditions, but there is no group for TB patients although they and the professionals have reported offering/receiving this action, respectively.…”
supporting
confidence: 75%
“…The existing scenario contrasts with the one proposed by the Ministry of Health, of easy access to diagnosis, care and HIV/AIDS treatment, and this deserves to be further investigated. Patients with TCD4+ cell count < 200 cells/mm 3 and asymptomatic tend not to adhere to HAART 16,35,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The social status may help explain the difficulties patients have to understand the importance of adherence. Social and economic factors, such as lack of resources and difficulties in commuting also limit access to health facilities, hampering the provision of health care and contributing to non-adherence 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge, perceptions, beliefs, and expectations that the patient has on the disease and its treatment may influence the way of dealing with the disease itself [50]. Other factors, such as anxiety about the possible adverse effects, the possibility of forgetting to take medication, the frustration with the health care team, and the lack of personal motivation, can also adversely affect the continuity of treatment [51].…”
Section: Impact On Lifementioning
confidence: 99%